Exposed polymer cement waterproof coating with capillary crystallization function and preparation method thereof

Through the formulation optimization design, an exposed polymer cement waterproof coating with permeation and crystallization function is provided, which solves the problem that traditional coatings cannot automatically repair microcracks and are not suitable for exposed use, and achieves efficient waterproofing effects inside and outside the structure.

CN119614033APending Publication Date: 2025-03-14ORIENTAL YUHONG BUILDING REPAIR TECH CO LTD

Patent Information

Application Number
CN202411726844.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-05
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional polymer cement waterproof coatings lack penetrating crystallization active materials, cannot produce secondary crystallization at base layer defects, automatically repair microcracks, and are usually not suitable for exposed use.

Method used

Through formulation optimization design, an exposed polymer cement waterproof coating including component A and component B is provided. Component A includes acrylic polymer emulsions, fluorocarbon emulsions, methyl silicic acid, soluble inorganic silicates and other additives; Component B includes cement, fillers, geopolymers, nano-scale silicon-containing compounds, cellulose ethers and pigments. This coating meets the standards of GB/T 23445-2009, GB 18445-2012 and JG/T375-2012, and has penetration crystallization function and high-strength waterproofing performance.

Benefits of technology

This waterproof coating has the function of permeation crystallization, can repair cracks inside the structure, enhance the waterproof performance of the structure, and form a high-strength waterproof layer on the outside, providing a comprehensive and long-term waterproof effect, and is suitable for exposed repair projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159406210000071
    Figure BDA0005159406210000071
  • Figure BDA0005159406210000072
    Figure BDA0005159406210000072
  • Figure BDA0005159406210000081
    Figure BDA0005159406210000081
Patent Text Reader

Abstract

The invention discloses an exposed polymer cement waterproof coating with a permeable crystallization function and a preparation method thereof. The waterproof coating comprises a component A and a component B, the component A comprises acrylic polymer emulsion, fluorocarbon emulsion, methyl silicic acid, soluble inorganic silicate and other auxiliaries; and the component B comprises cement, a filler, a geopolymer, a nanoscale silicon-containing compound, cellulose ether and an optional pigment. The waterproof coating disclosed by the invention has the functions of repairing structural cracks by permeable crystallization in the structure and enhancing the waterproof function of the structure; the high-elasticity and high-strength coating film outside the structure has an external waterproof effect, and the structure is protected; and meanwhile, the comprehensive long-acting waterproof effect is achieved through the self-repairing function when the coating film is broken. The LED lamp has exposure performance, and is particularly suitable for maintenance engineering needing to be exposed and repaired.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of waterproof coatings, and more specifically, relates to an exposed polymer cement waterproof coating with a penetration crystallization function and a preparation method thereof. Background Art

[0002] Polymer cement waterproof coating is a two-component, water-based building waterproof coating made by rationally proportioning and compounding inorganic powders composed of cement, quartz sand, light and heavy calcium carbonate and other inorganic fillers and various additives.

[0003] Traditional polymer cement waterproof coatings achieve waterproofing through a dense coating layer of 1.5mm thick. They do not have the ability to penetrate and crystallize active materials, and therefore do not have the ability to make the active substances sealed in the coating produce secondary crystallization at the defects of the base layer after contact with water and automatically repair defects such as microcracks. At the same time, traditional polymer cement waterproof coatings are usually used in non-exposed use scenarios, where the surface needs to be tiled or an exposed protective layer needs to be added. Summary of the invention

[0004] The purpose of the present invention is to provide an exposed polymer cement waterproof coating with a penetration crystallization function and a preparation method thereof. The present invention optimizes the formula design so that the waterproof coating of the present invention has good penetration crystallization function and waterproof performance, and can meet the requirements of exposed use.

[0005] In order to achieve the above-mentioned object, one aspect of the present invention provides an exposed polymer cement waterproof coating with a penetration crystallization function, the waterproof coating comprising component A and component B;

[0006] The component A comprises: acrylic polymer emulsion, fluorocarbon emulsion, methylsilicic acid, soluble inorganic silicate and other additives;

[0007] The B component comprises cement, filler, geopolymer, nano-sized silicon-containing compound, cellulose ether and optional pigment.

[0008] In the present invention, the exposed polymer cement waterproof coating with penetrating crystallization function meets the standards of GB / T 23445-2009 "Polymer Cement Waterproof Coating" and GB 18445-2012 "Cement-based Penetrating Crystallization Waterproof Coating", and meets the aging resistance of JG / T375-2012 "Metal Roof Acrylic High Elastic Waterproof Coating", and has rigid-flexible integrated waterproof characteristics; the penetrating crystallization function can penetrate into the structure to repair structural cracks, etc. In the structure, the crystal is a continuous reaction crystallization generation process, which can fill the structural gap, enhance the structural strength, and improve the structural waterproof function. At the same time, the crystal can improve the rigid waterproof effect of the outer layer of the structure, and the flexible coating can form a 1.5mm thick high-strength waterproof layer on the outside of the structure, so that the comprehensive functionality of structural waterproof enhancement, rigid waterproof, and flexible coating waterproof can be formed, and the overall waterproof effect and safety can be improved. The outer coating waterproof layer has long-term activity, and in a humid environment, it can repair small cracks caused by structural settlement and other reasons in 7 to 30 days, which is different from the traditional polymer cement waterproof coating and can achieve a long-term waterproof effect. At the same time, this "trinity" waterproof coating product not only has the functions of penetration and crystallization, and the functions of polymer cement waterproof coating, but can also meet the needs of exposed use. The coordinated combination of the three functions is particularly suitable for the needs of exposed repair projects of existing buildings.

[0009] According to the present invention, preferably, based on the total weight of the component A, the component A comprises: 45-80wt% of acrylic polymer emulsion, 5-30wt% of fluorocarbon emulsion, 5-15wt% of methylsilicic acid, 1-8wt% of soluble inorganic silicate and 1.6-5.6wt% of other additives, and the sum of the weight percentages of the components is 100%;

[0010] Based on the total weight of the B component, the B component includes: 15-25wt% cement, 0-5wt% pigment, 40-70wt% filler, 15-20wt% geopolymer, 1-4.5wt% nano-scale silicon-containing compound and 0.2-0.5wt% cellulose ether, and the sum of the weight percentages of the various components is 100%.

[0011] According to the present invention, preferably, the acrylic polymer emulsion comprises: at least one of pure acrylic emulsion, styrene acrylic emulsion and silicone acrylic emulsion.

[0012] According to the present invention, preferably, the soluble inorganic silicate comprises at least one of lithium silicate, sodium silicate, magnesium silicate and potassium silicate.

[0013] According to the present invention, preferably, the nano-scale silicon-containing compound is nano-scale microsilicon powder and / or nano-silicon dioxide.

[0014] According to the present invention, preferably, the nano-scale silicon-containing compound is nano-scale microsilicon powder and nano-silicon dioxide, and the mass ratio of the nano-scale microsilicon powder to nano-silicon dioxide is (3-4):1.

[0015] In the present invention, the particle size of the nano-scale silicon-containing compound is preferably 4000-5000 mesh.

[0016] According to the present invention, preferably, the cement comprises: at least one of silicate cement, sulphoaluminium cement and high alumina cement;

[0017] The pigment is titanium dioxide;

[0018] The filler comprises: at least one of quartz sand, heavy calcium and talcum powder;

[0019] The geopolymer comprises: calcined kaolin and / or fly ash;

[0020] The cellulose ether includes at least one of hydroxyethyl cellulose ether, hydroxypropyl cellulose ether and hydroxypropyl methyl cellulose ether.

[0021] According to the present invention, preferably, the other additives include at least one of a defoamer, a dispersant, a leveling agent, a coupling agent and a preservative;

[0022] Preferably, based on the total weight of the component A, the other additives include: 0.1-0.5wt% of a defoamer, 0.1-0.5wt% of a dispersant, 0.2-0.6wt% of a leveling agent, 1-3wt% of a coupling agent and 0.2-0.6wt% of a preservative.

[0023] According to the present invention, preferably, the mass ratio of component A to component B is 1:(1-3).

[0024] In the present invention, the mass ratio of component A to component B can be adjusted according to the use environment. Preferably, 1:1 is used for base treatment; 1:1.5 or 1:2 is used for base waterproofing with large activity; 1:2 or 1:2.5 is used for base waterproofing with small activity; 1:3 is used for long-term water immersion environment or underground engineering waterproofing.

[0025] In the present invention, the conventional polymer cement waterproof coating can be used for construction. For example, the use method of the exposed polymer cement waterproof coating with penetrating crystallization function is as follows: 1) Base cleaning: The waterproof base should be flat, solid, dry, without sharp bumps, honeycombs, pockmarks and peeling, without oil stains and floating dust. The cracks, base deformation joints, and grooves left at the pipe roots should be filled with sealing materials and additional waterproof treatment should be done. The flat and solid base does not need to be coated with a base treatment agent. Additional waterproof layer for details: The basic details such as the corners, pipe roots, and deformation joints should first be constructed with an additional waterproof layer, which can be applied 2 to 4 times (thickness not less than 1mm). If the carcass needs to be sandwiched or the butyl tape reinforcement material needs to be pasted, it must be soaked. A layer of polyester non-woven fabric should be added to the deformation joints first, and then the coating should be applied to form an additional waterproof layer empty paving structure.

[0026] 2) Primer preparation and construction: first add the liquid material of component A into the mixing bucket, then add the powder material of component B while stirring, component A: component B = 1:1, stirring time is about 10 minutes. After the primer penetrates and the surface of the base is moist, the paint can be applied (1 kg can be applied for 2 m 2 The paint application should be carried out while primer is applied.

[0027] 3) Large surface construction: Add the liquid and powder components into the mixing bucket in the ratio of 1:1.5~3 (mass ratio), stir for about 10 minutes, and apply the paint while applying the primer.

[0028] Another aspect of the present invention provides a method for preparing the above-mentioned exposed polymer cement waterproof coating with penetration crystallization function, the preparation method comprising:

[0029] The acrylic polymer emulsion, fluorocarbon emulsion, methyl silicic acid, soluble inorganic silicate and other additives are mixed uniformly to obtain the component A;

[0030] The cement, filler, geopolymer, nano-sized silicon-containing compound, cellulose ether and optional pigment are mixed uniformly to obtain the B component.

[0031] In the present invention, as a preferred embodiment, the preparation of component A: add acrylic polymer emulsion, fluorocarbon emulsion, methylsilicic acid, and some additives according to the ratio, stir at 400-600rpm for 5-10min until uniform; then add soluble inorganic silicate and the remaining additives in sequence according to the ratio, disperse at 300-500rpm for 10-20min until uniform;

[0032] Preparation of component B: Add cement, filler, geopolymer, nano-silicon compound, cellulose ether and optional pigment in order according to the proportion, and disperse at 15-30 r / min for 10-20 minutes until uniform.

[0033] The technical solution of the present invention has the following beneficial effects:

[0034] (1) The waterproof coating of the present invention has the function of penetrating crystals inside the structure to repair structural cracks and enhance the waterproof function of the structure; the high elasticity and high strength coating outside the structure plays an external waterproof role to protect the structure; at the same time, the self-repair function of the coating film fracture achieves a comprehensive long-term waterproof effect. It has the performance of being exposed, and is particularly suitable for maintenance projects that require exposed repair.

[0035] (2) The waterproof coating product of the present invention is green, environmentally friendly, non-toxic and harmless. It is a two-component product with flexible application and can be formulated according to actual application. At the same time, it is easy to construct and can be sprayed, brushed, rolled, etc.

[0036] (3) The waterproof coating product of the present invention can be formulated into different performance models according to different application scenarios, and can be widely used as a waterproof coating with penetration and crystallization function for concrete structures, including but not limited to underground space projects, roofs, kitchens and bathrooms, sewage pools, water conservancy projects, tunnel projects, etc.

[0037] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0039] The present invention is further described below by examples:

[0040] In the following embodiments and comparative examples:

[0041] The fluorocarbon emulsion used was purchased from Arkema with the brand name FMA-12; the pure acrylic emulsion was purchased from BASF with the brand name 3587; the styrene acrylic emulsion was purchased from BASF with the brand name S400F; the defoaming agent was purchased from Nopco with the brand name NXZ; the dispersant was purchased from Dow with the brand name 731A; the leveling agent was purchased from Dow with the brand name RM-8W; the coupling agent was purchased from Covestro with the brand name KH550; the preservative was Kason, purchased from Thor with the brand name MV; the particle size of quartz sand was 325 mesh; the particle size of heavy calcium was 800 mesh; the particle size of talc was 1250 mesh; the particle size of nano-scale microsilica powder was 5000 mesh; the particle size of nano-silicon dioxide was 5000 mesh; hydroxypropyl cellulose ether was purchased from Heda with a viscosity of 25,000; and hydroxypropyl methyl cellulose ether was purchased from Heda with a viscosity of 40,000.

[0042] The test items of the following embodiments and comparative examples are:

[0043] Untreated tensile strength, untreated elongation at break, untreated bonding strength and water impermeability are all tested in accordance with GB / T23445-2008 "Polymer Cement Waterproof Coating";

[0044] The mortar seepage pressure ratio (with coating), mortar seepage pressure ratio (without coating), concrete seepage pressure ratio (with coating), concrete seepage pressure ratio (without coating), and the second seepage pressure of coated concrete are all tested in accordance with GB18445-2012 "Cement-based penetrating crystalline waterproof material";

[0045] Artificial weathering treatment is tested in accordance with JG / T375-2012 "Metal Roof Acrylic High Elastic Waterproof Coating".

[0046] Example 1

[0047] This embodiment provides an exposed polymer cement waterproof coating with a penetration crystallization function, which is as follows:

[0048] Based on the total weight of component A, component A includes: 20wt% of fluorocarbon emulsion, 60wt% of pure acrylic emulsion, 10wt% of methylsilicic acid, 4wt% of lithium silicate, 3wt% of sodium silicate, 0.2wt% of defoamer, 0.2wt% of dispersant, 0.3wt% of leveling agent, 2wt% of coupling agent, and 0.3wt% of preservative;

[0049] Based on the total weight of component B, component B includes: 20wt% of PO42.5 silicate cement, 47wt% of quartz sand, 3wt% of titanium dioxide, 10wt% of heavy calcium carbonate, 17wt% of calcined kaolin, 2wt% of nano-scale microsilica powder, 0.5wt% of nano-silicon dioxide, and 0.5wt% of hydroxypropyl cellulose ether.

[0050] The specific preparation method of the waterproof coating is as follows:

[0051] Preparation of component A: Add pure acrylic emulsion, fluorocarbon emulsion, methylsilicic acid, defoamer, and dispersant according to the proportion, stir at 500 rpm for 8 minutes until the mixture is evenly mixed; then add lithium silicate, sodium silicate, leveling agent, coupling agent, and preservative in sequence according to the proportion, disperse at 400 rpm for 15 minutes until the mixture is evenly mixed;

[0052] Preparation of component B: Add in order according to the ratio: PO42.5 silicate cement, titanium dioxide, quartz sand, heavy calcium, calcined kaolin, nano-silica powder, nano-silicon dioxide and hydroxypropyl cellulose ether, and disperse at 20r / min for 15min until mixed evenly.

[0053] Component A and component B were mixed at a mass ratio of 1:1.5, and the obtained coating was subjected to performance testing. The specific test results are as follows:

[0054] Table 1

[0055]

[0056] Example 2

[0057] The difference between this embodiment and embodiment 1 is that component A and component B are mixed in a mass ratio of 1:2, and the rest is the same as embodiment 1. The prepared coating was subjected to performance testing, and the specific test results are as follows:

[0058] Table 2

[0059]

[0060] Example 3

[0061] This embodiment provides an exposed polymer cement waterproof coating with a penetration crystallization function, which is as follows:

[0062] Based on the total weight of component A, component A includes: 20wt% of fluorocarbon emulsion, 53wt% of styrene acrylic emulsion, 15wt% of methyl silicate, 5wt% of lithium silicate, 3wt% of magnesium silicate, 0.5wt% of defoamer, 0.2wt% of dispersant, 1wt% of leveling agent, 2wt% of coupling agent, and 0.3wt% of preservative;

[0063] Based on the total weight of component B, component B includes: 15wt% of sulphoaluminum cement, 54wt% of quartz sand, 3wt% of titanium dioxide, 9wt% of talc, 15wt% of calcined kaolin, 3wt% of nano-scale microsilica powder, 0.8wt% of nano-silicon dioxide, and 0.2wt% of hydroxypropyl methylcellulose ether.

[0064] The specific preparation method of the waterproof coating is as follows:

[0065] Preparation of component A: Add styrene acrylic emulsion, fluorocarbon emulsion, methylsilicic acid, defoamer, and dispersant according to the ratio, stir at 500 rpm for 8 minutes until the mixture is evenly mixed; then add lithium silicate, magnesium silicate, leveling agent, coupling agent, and preservative in sequence according to the ratio, disperse at 400 rpm for 15 minutes until the mixture is evenly mixed;

[0066] Preparation of component B: Add the following components in order according to the proportion: sulphoaluminium cement, titanium dioxide, quartz sand, talcum powder, calcined kaolin, nano-silica powder, nano-silicon dioxide and hydroxypropyl methylcellulose ether, and disperse at 20 r / min for 15 minutes until the mixture is evenly mixed.

[0067] Component A and component B were mixed in a mass ratio of 1:3, and the obtained coating was subjected to performance testing. The specific test results are as follows:

[0068] Table 3

[0069]

[0070]

[0071] Comparative Example 1

[0072] This comparative example provides an exposed polymer cement waterproof coating with a penetrating crystallization function, which is as follows:

[0073] Based on the total weight of component A, component A includes: 20wt% of fluorocarbon emulsion, 60wt% of pure acrylic emulsion, 9wt% of lithium silicate, 8wt% of sodium silicate, 0.2wt% of defoamer, 0.2wt% of dispersant, 0.3wt% of leveling agent, 2wt% of coupling agent, and 0.3wt% of preservative;

[0074] Based on the total weight of component B, component B includes: 20wt% of PO42.5 silicate cement, 50wt% of quartz sand, 3wt% of titanium dioxide, 10wt% of heavy calcium carbonate, 17wt% of calcined kaolin, 2wt% of nano-scale microsilica powder, 0.5wt% of nano-silicon dioxide, and 0.5wt% of hydroxypropyl cellulose ether.

[0075] The specific preparation method of the waterproof coating is as follows:

[0076] Preparation of component A: Add pure acrylic emulsion, fluorocarbon emulsion, defoamer, and dispersant according to the ratio and stir at 500 rpm for 8 minutes until the mixture is evenly mixed; then add lithium silicate, sodium silicate, leveling agent, coupling agent, and preservative in sequence according to the ratio and disperse at 400 rpm for 15 minutes until the mixture is evenly mixed;

[0077] Preparation of component B: Add in order according to the ratio: PO42.5 silicate cement, titanium dioxide, quartz sand, heavy calcium, calcined kaolin, nano-silica powder, nano-silicon dioxide and hydroxypropyl cellulose ether, and disperse at 20r / min for 15min until mixed evenly.

[0078] Component A and component B were mixed at a mass ratio of 1:1.5, and the obtained coating was subjected to performance testing. The specific test results are as follows:

[0079] Table 4

[0080]

[0081]

[0082] Comparative Example 2

[0083] This comparative example provides an exposed polymer cement waterproof coating with a penetrating crystallization function, which is as follows:

[0084] Based on the total weight of component A, component A includes: 20wt% of fluorocarbon emulsion, 60wt% of pure acrylic emulsion, 10wt% of methylsilicic acid, 4wt% of lithium silicate, 3wt% of sodium silicate, 0.2wt% of defoamer, 0.2wt% of dispersant, 0.3wt% of leveling agent, 2wt% of coupling agent, and 0.3wt% of preservative;

[0085] Based on the total weight of component B, component B includes: 22.5wt% of PO42.5 silicate cement, 50wt% of quartz sand, 3wt% of titanium dioxide, 10wt% of heavy calcium, 17wt% of calcined kaolin, and 0.5wt% of hydroxypropyl cellulose ether.

[0086] The specific preparation method of the waterproof coating is as follows:

[0087] Preparation of component A: Add pure acrylic emulsion, fluorocarbon emulsion, methylsilicic acid, defoamer, and dispersant according to the proportion, stir at 500 rpm for 8 minutes until the mixture is evenly mixed; then add lithium silicate, sodium silicate, leveling agent, coupling agent, and preservative in sequence according to the proportion, disperse at 400 rpm for 15 minutes until the mixture is evenly mixed;

[0088] Preparation of component B: Add PO42.5 silicate cement, titanium dioxide, quartz sand, heavy calcium, calcined kaolin and hydroxypropyl cellulose ether in order according to the proportion, and disperse at 20r / min for 15min until mixed evenly.

[0089] Component A and component B were mixed at a mass ratio of 1:1.5, and the obtained coating was subjected to performance testing. The specific test results are as follows:

[0090] Table 5

[0091]

[0092] Comparative Example 3

[0093] This embodiment provides a polymer cement waterproof coating with a penetration crystallization function, which is as follows:

[0094] Based on the total weight of component A, component A includes: 80wt% pure acrylic emulsion, 10wt% methylsilicic acid, 4wt% lithium silicate, 3wt% sodium silicate, 0.2wt% defoamer, 0.2wt% dispersant, 0.3wt% leveling agent, 2wt% coupling agent, and 0.3wt% preservative;

[0095] Based on the total weight of component B, component B includes: 20wt% of PO42.5 silicate cement, 50wt% of quartz sand, 3wt% of titanium dioxide, 10wt% of heavy calcium carbonate, 17wt% of calcined kaolin, 2wt% of nano-scale microsilica powder, 0.5wt% of nano-silicon dioxide, and 0.5wt% of hydroxypropyl cellulose ether.

[0096] The specific preparation method of the waterproof coating is as follows:

[0097] Preparation of component A: Add pure acrylic emulsion, methylsilicic acid, defoamer, and dispersant according to the ratio and stir at 500 rpm for 8 minutes until the mixture is evenly mixed; then add lithium silicate, sodium silicate, leveling agent, coupling agent, and preservative in sequence according to the ratio and disperse at 400 rpm for 15 minutes until the mixture is evenly mixed;

[0098] Preparation of component B: Add in order according to the ratio: PO42.5 silicate cement, titanium dioxide, quartz sand, heavy calcium, calcined kaolin, nano-silica powder, nano-silicon dioxide and hydroxypropyl cellulose ether, and disperse at 20r / min for 15min until mixed evenly.

[0099] Component A and component B were mixed at a mass ratio of 1:1.5, and the obtained coating was subjected to performance testing. The specific test results are as follows:

[0100] Table 6

[0101]

[0102] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. An exposed polymer cement waterproof coating with penetration and crystallization function, characterized in that: The waterproof coating comprises component A and component B; The component A comprises: acrylic polymer emulsion, fluorocarbon emulsion, methylsilicic acid, soluble inorganic silicate and other additives; The B component comprises cement, filler, geopolymer, nano-sized silicon-containing compound, cellulose ether and optional pigment.

2. The waterproof coating according to claim 1, wherein: Based on the total weight of the component A, the component A comprises: 45-80wt% of acrylic polymer emulsion, 5-30wt% of fluorocarbon emulsion, 5-15wt% of methylsilicic acid, 1-8wt% of soluble inorganic silicate and 1.6-5.6wt% of other additives, and the sum of the weight percentages of the components is 100%; Based on the total weight of the B component, the B component includes: 15-25wt% cement, 0-5wt% pigment, 40-70wt% filler, 15-20wt% geopolymer, 1-4.5wt% nano-scale silicon-containing compound and 0.2-0.5wt% cellulose ether, and the sum of the weight percentages of the various components is 100%.

3. The waterproof coating according to claim 1 or 2, wherein: The acrylic polymer emulsion includes at least one of pure acrylic emulsion, styrene acrylic emulsion and silicone acrylic emulsion.

4. The waterproof coating according to claim 1 or 2, wherein: The soluble inorganic silicate includes at least one of lithium silicate, sodium silicate, magnesium silicate and potassium silicate.

5. The waterproof coating according to claim 1 or 2, wherein: The nano-scale silicon-containing compound is nano-scale microsilicon powder and / or nano-silicon dioxide.

6. The waterproof coating according to claim 5, wherein: The nano-scale silicon-containing compound is nano-scale microsilicon powder and nano-silicon dioxide, and the mass ratio of the nano-scale microsilicon powder to nano-silicon dioxide is (3-4):

1.

7. The waterproof coating according to claim 1 or 2, wherein: The cement comprises: at least one of silicate cement, sulphoaluminium cement and high alumina cement; The pigment is titanium dioxide; The filler comprises: at least one of quartz sand, heavy calcium and talcum powder; The geopolymer comprises: calcined kaolin and / or fly ash; The cellulose ether includes at least one of hydroxyethyl cellulose ether, hydroxypropyl cellulose ether and hydroxypropyl methyl cellulose ether.

8. The waterproof coating according to claim 1 or 2, wherein: The other additives include at least one of a defoamer, a dispersant, a leveling agent, a coupling agent and a preservative; Preferably, based on the total weight of component A, the other additives include: 0.1-0.5wt% of defoamer, 0.1-0.5wt% of dispersant, 0.2-1wt% of leveling agent, 1-3wt% of coupling agent and 0.2-0.6wt% of preservative.

9. The waterproof coating according to claim 1 or 2, wherein: The mass ratio of component A to component B is 1:(1-3).

10. The method for preparing the exposed polymer cement waterproof coating with penetration crystallization function according to any one of claims 1 to 9, characterized in that: The preparation method comprises: The acrylic polymer emulsion, fluorocarbon emulsion, methyl silicic acid, soluble inorganic silicate and other additives are mixed uniformly to obtain the component A; The cement, filler, geopolymer, nano-sized silicon-containing compound, cellulose ether and optional pigment are mixed uniformly to obtain the B component.

Citation Information

Patent Citations

  • Polymer cement waterproof coating

    CN103694830A

  • Cement-based capillary crystalline waterproof material based on nanosilicon-based material and preparation method and application thereof

    CN110105025A

Cited By

  • Micro cement coating and preparation method thereof

    CN121086605A

  • Water-based inorganic coating for concrete structure and preparation method of water-based inorganic coating

    CN121975360A